Movement of Exocortis Virus in Citrus Plants - FUDL-ALLAH, ABD EL-SHAFY A. (The Libyan Journal of Agriculture, 2023)
The exocortis virus failed to move up or down across any girdle within nine months after inoculation. Any amount of bark bridging permitted the exocortis virus to cross. Plants inoculated with the inner bark portions showed symptoms two months after inoculation while plants inoculated with the outer bark portions showed symptoms, if any, ten months after inoculation. Results indicate that exocortis virus moves through the bark and is mainly phloem limited.